Vermicomposting evaluation of different combinations of organic waste using Perionyx excavates - Huntley, Sona; Abdullah Adil Ansari (International journal of recycling of organic waste in agriculture, 2021)
Purpose Organic waste is a serious concern across the globe contributed by human activity that can be managed by efficient process like vermicomposting which can reduce the waste that is dumped in landfills into useful product vermicompost. This research was conducted to study the bio-conversion of organic waste (fruit and vegetable waste) using Perionyx excavatus into quality vermicompost. Method Three organic waste treatments were used for the vermicomposting process: FW [Fruit waste + Cow Dung], VW [Vegetable waste + Cow Dung], FVW [Fruit waste + Vegetable waste + Cow Dung]. A control group was set up without earthworms for each treatment. The compost was harvested after 38 days, weighed and the rate of production per day was calculated. The harvested compost was then subjected to physico-chemical analysis to determine the nutrient status. Results The experimental group had a significant rate of production with higher quantity than the control groups. Vermicompost produced from vegetable waste was 515.45 g (51.55%) which was the highest among all the treatments. The lowest amount of compost was produced by the Fruit + Vegetable waste treatment in the control group (184.16 g). The nutrient status was within the acceptable range for the experimental groups. Conclusion Epigeic earthworm Perionyx excavatus is highly efficient in reducing organic waste (fruit and vegetable waste) into vermicompost enriched with nutrients necessary for plant growth.